Differentiated Instruction Based on Lesson Study to Improve Critical Thinking and Collaborative Skills in EFL Class - Rizkariani Sulaiman; Umar Mansyur; Hilal Surahmatullah; Elena Tikhonova (Universitas Cokroaminoto Palopo, 2026)
This classroom action research aimed to investigate how differentiated Instruction using Lesson Study enhances students’ critical thinking and teamwork skills in learning English. The study took place in class 8.2 at UPT SPF SMP Negeri 23 Makassar, Indonesia, during the 2025/2026 school year, involving 37 eighth-grade students. Two cycles of Lesson Study-based action research (Plan-Do-See and Re-Plan-Do-See) were carried out, focusing on teaching the simple past tense, recount texts, and modals expressing ability or inability. Instruction was tailored based on students’ readiness, interests, and learning styles (visual, auditory, kinesthetics). Data collection included rubrics for critical thinking and collaboration, classroom observations, and field notes. Quantitative results showed consistent growth in students’ critical thinking. The average score increased from 2.3 (Sufficient) before the intervention to 2.8 (Good) after Cycle I and to 3.3 (Very Good) after Cycle II (scale 1–4). The percentage of students meeting the mastery criterion (score ≥ 3.0) rose from 13.5% to 54.1% and then to 81.1%. Collaboration skills also improved, with the average score rising from 2.5 (Sufficient) to 3.0 (Good) and 3.4 (Very Good), with a shift from most students in the Sufficient category to most in the Good–Very Good categories. Qualitative data revealed changes from one-student-dominant group work and brief, unsupported answers to more shared participation, clearer roles, reasoned arguments, and reflective group discussions. These findings suggest that differentiated instruction within a Lesson Study cycle effectively promotes critical thinking and collaboration in junior high school EFL classes and aligns with the goals of the Kurikulum Merdeka and 21st-century skills.